Medicines management in the Philippine public sector during the response to Haiyan - Roderick Salenga; Yolanda Robles; Monet Loquias; Francis Capule; Anna Melissa Guerrero (World Health Organization Regional Office for the Western Pacific, 2015)
Introduction: Health service delivery in the Philippines is constantly challenged by disasters and emergencies. This descriptive study documented existing policies for medicines management in the Philippines and then assessed these in the public sector response post-Haiyan. Method: We used desk a review of existing laws, regulations and related issuances and a series of interviews of key informants from various national and local health agencies. Results: We found that while numerous national policies covered critical aspects of medicines management, implementation post-Haiyan was problematic at all levels of the decentralized health-care system. We identified issues of quantification, warehousing, distribution, utilization monitoring and disposal. Donated medicines also added additional burden for storage and disposal, especially for expired and unwanted medicines. Discussion: While the process of managing medicines during disasters did not differ greatly from non-emergency situations, the Haiyan experience highlighted the system's weaknesses. With the current gaps in implementation, as well as the logistical obstacles brought about by disasters, there is a need to have integrated mechanisms for medicines management in the Philippines. This assessment provided an important opportunity to review the medicines management policies at national and local levels.